Quality of Work Life in Commercial Banks of Butwal: An Investigation of Key Determinants - Lamichhane, Barsha (The Lumbini Journal of Business and Economics, 2025)
Purpose: The purpose of this study is to look at the impact of health and well-being, recognition for career advancement, job satisfaction, interpersonal relationships, work-life balance, fair compensation, and learning and development on the quality of life in commercial banks. Methods: The study used descriptive and causal comparative research design, supplemented with a wide range of statistical measures such as mean, standard deviation, correlation, independent t test, one-way ANOVA, Mann-Whitney U test, and Kruskal-Wallis H test. Data was collected using a purposive sampling strategy, with 192 commercial bank workers targeted. Results: The research finds that learning and growth are the most important predictors of workplace quality. Conclusion: This study suggests that in order to sustain employee quality of life, commercial banks must prioritize learning and development as well as job satisfaction.